Bone Morphogenetic Protein 9 Reduces Cardiac Fibrosis and Improves Cardiac Function in Heart Failure - Morine, Kevin J.; Qiao, Xiaoying; York, Sam; Natov, Peter S.; Paruchuri, Vikram; Zhang, Yali; Aronovitz, Mark J.; Karas, Richard H.; Kapur, Navin K. (Circulation (New York, N.Y.), 2018)
BACKGROUND—Heart failure is a growing cause of morbidity and mortality worldwide. Transforming growth factor beta (TGF-β1) promotes cardiac fibrosis, but also activates counter-regulatory pathways that serve to regulate TGF-β1 activity in heart failure. Bone morphogenetic protein 9 (BMP9) is a member of the TGFβ family of cytokines and signals via the downstream effector protein Smad1. Endoglin is a TGFβ co-receptor that promotes TGF-β1 signaling via Smad3 and binds BMP9 with high affinity. We hypothesized that BMP9 limits cardiac fibrosis by activating Smad1 and attenuating Smad3 and further that neutralizing endoglin activity promotes BMP9 activity. METHODS—We examined BMP9 expression and signaling in human cardiac fibroblasts and human subjects with heart failure. We utilized the thoracic aortic constriction (TAC) induced model of heart failure to evaluate the functional effect of BMP9 signaling on cardiac remodeling. RESULTS—BMP9 expression is increased in the circulation and left ventricle (LV) of human subjects with heart failure and is expressed by cardiac fibroblasts. Next, we observed that BMP9 attenuates Type I collagen synthesis in human cardiac fibroblasts using recombinant human BMP9 and an siRNA approach. In BMP9 mice subjected to TAC, loss of BMP9 activity promotes cardiac fibrosis, impairs LV function, and increases LV levels of phosphorylated Smad3 (pSmad3), not pSmad1. In contrast, treatment of wild-type mice subjected to TAC with recombinant BMP9 limits progression of cardiac fibrosis, improves LV function, enhances myocardial capillary density, and increases LV levels of pSmad1, not pSmad3 compared to vehicle treated controls. Since endoglin binds BMP9 with high affinity, we explored the effect of reduced endoglin activity on BMP9 activity. Neutralizing endoglin activity in human cardiac fibroblasts or in wild-type mice subjected to TAC induced heart failure limits collagen production, increases BMP9 protein levels, and increases levels of pSmad1, not pSmad3. CONCLUSIONS—Our results identify a novel functional role for BMP9 as an endogenous inhibitor of cardiac fibrosis due to LV pressure overload and further show that treatment with either recombinant BMP9 or disruption of endoglin activity promotes BMP9 activity and limits cardiac fibrosis in heart failure, thereby providing potentially novel therapeutic approaches for patients with heart failure.